2018
DOI: 10.1080/10428194.2018.1485905
|View full text |Cite
|
Sign up to set email alerts
|

TCR αβ+/CD19+ cell depletion in haploidentical hematopoietic allogeneic stem cell transplantation: a review of current data

Abstract: Allogeneic hematopoietic stem cell transplantation is a curative option for patients with a variety of diseases. Transplantation from a related haploidentical donor is being increasingly utilized for patients who lack an available human leukocyte antigen matched related or unrelated donor. One of the strategies used for haploidentical transplants involves selective depletion of T cells expressing the αβ T cell receptor and CD19+ B cells prior to transplant. This allows for the removal of cells responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Recently, the immunomagnetic depletion of TCRαβ + T- and CD19 + B cells cells has evolved to a fully automated and GMP-compliant operating procedure. Several single and multicenter retrospective studies already reported the safety and feasibility of TCRαβ/CD19 depletion as graft engineering approach [ 16 , 18 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the immunomagnetic depletion of TCRαβ + T- and CD19 + B cells cells has evolved to a fully automated and GMP-compliant operating procedure. Several single and multicenter retrospective studies already reported the safety and feasibility of TCRαβ/CD19 depletion as graft engineering approach [ 16 , 18 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a need for research exploring how to maximize the anti-leukemic effects of the graft while removing the GvHD effect of transplanted cells 24 . One of the current methods for haploidentical transplantation is TCR αβ+/CD19+ cell depletion, in which there is a selective depletion of T cells expressing the αβ T cell receptor (TCR) and CD19+ B cells before transplantation, as these cells are responsible for GvHD [25][26][27] . However, T cells expressing γδ TCR are retained as γδ T cells are able to produce the GVT effect without causing GvHD 25,27 .…”
Section: Haploidentical Transplantation (Table 2)mentioning
confidence: 99%
“…One of the current methods for haploidentical transplantation is TCR αβ+/CD19+ cell depletion, in which there is a selective depletion of T cells expressing the αβ T cell receptor (TCR) and CD19+ B cells before transplantation, as these cells are responsible for GvHD [25][26][27] . However, T cells expressing γδ TCR are retained as γδ T cells are able to produce the GVT effect without causing GvHD 25,27 . In one study, thirty-seven patients with primary immunodeficiency (PID) received transplants from a matched unrelated donor (MUD) or haploidentical mismatched related donor (MMRD), with all grafts being TCR αβ+/CD19+ depleted 28 .…”
Section: Haploidentical Transplantation (Table 2)mentioning
confidence: 99%
“…65 In haploidentical transplantation, the graft contains lower of T-cell content to diminish GVHD. 66 Outcomes of haploidentical HSCT may be affected by innate immune cells like T cells and natural-killer cells. 67 In high-risk acute leukemia, the applicabilion of HLA-haploidentical HSCT is elevated.…”
Section: Umbilical Cord Blood Cells and Haploidentical Transplantatiomentioning
confidence: 99%